TO EAT OR NOT TO EAT...IN VIGO:: THE TRANSLATOR SOLVES THE DILEMMA - Oya, Elisabet García; González, Rebeca Cristina López (Belas Infiéis, 2015)
What happens when a cruise tourist arrives in Vigo (Galicia-Spain) and feels culture-hungry enough to explore the local cuisine? There are two possible ways to go about it: walking around the port area and trying some of the exquisite dishes which are kindly offered by the surrounding caterers, or with modern day technology surfing the city’s websites, for example, http://www.turismodevigo.org. Precisely here, some of the information offered deals with typical food any visitor can taste and includes recipes and information about food festivals. “[A]s all our behaviour is culture-specific” (Vermeer, 1994, p. 10), this paper aims to discuss how the translation of food on this mainstream website translated from either Spanish or Galician (or both) into English and Portuguese, yet not into French or Italian, can encourage or discourage visitors from savouring some of the most typical Galician dishes. One of the challenges of Translation Studies is dealing with cross-cultural references, which always increase the difficulty of transferring content from one language to another. The specific cultural barriers related to food might lead the translator to modify, adapt or even omit some of the content in order to make the translation (and explicitly the food) more delectable.